Characterization and land application of red gypsum: a waste product from the titanium dioxide industry - Ishak, Che Fauziah; S., Zauyah; Talib, Jamal (Elsevier, 1996)
A waste product from the titanium dioxide industry was analysed for its composition because of its potential use as a soil amendment in Malaysia. Under scanning electron microscopy (SEM), the gypsum crystals are present as tabular crystals of radiating elongated crystals in a matrix of calcite and iron oxides. The X-ray diffractogram (XRD) pattern of the iron concentrates shows the presence of goethite and hematite. The calcium content of red gypsum is 18.9% and the trace elements determined in this study (As, B, Cd, Cr, Cu, Ni and Pb) are present in low concentrations. A dissolution kinetics study indicates that the rate of red gypsum dissolution increases with decreasing particle size. On the other hand, Fe which is the other dominant element, exists in the non-soluble form. For the flocculation series test, only soils with a high percentage of water-dispersible clay (WDC) gave a positive effect of red gypsum on flocculation. Using the normal t-test, application of 10 Mg/ha of red gypsum on a Bungor soil series (16% WDC of bulk soil, a highly dispersive soil) was statistically significant (P = 0.1) in reducing runoffs, and total soil loss was reduced by > 30% compared with the control plot.